If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2 + -1k) = 2(y + 2) (2 * 3 + -1k * 3) = 2(y + 2) (6 + -3k) = 2(y + 2) Reorder the terms: 6 + -3k = 2(2 + y) 6 + -3k = (2 * 2 + y * 2) 6 + -3k = (4 + 2y) Solving 6 + -3k = 4 + 2y Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -3k = 4 + -6 + 2y Combine like terms: 6 + -6 = 0 0 + -3k = 4 + -6 + 2y -3k = 4 + -6 + 2y Combine like terms: 4 + -6 = -2 -3k = -2 + 2y Divide each side by '-3'. k = 0.6666666667 + -0.6666666667y Simplifying k = 0.6666666667 + -0.6666666667y
| 5x+14=2x+3x+14 | | 4k-11k+4=2k^2 | | 3j-18=-6p | | 4x^2-12x=(2x^2-3)-9 | | 12p-8=-4p | | x(5x-18)+90=180 | | (4x-10)=(135) | | 58=2(m+4)+m | | 4(2x-3)-5(3x+1)=4 | | -3+3y+3=3y | | sin(33)=14/x | | .071*33sin=x | | 123(X)-65=567-28 | | 4x(4x)=5x+10 | | 10x-12=x+2 | | 400=2(x+59)+2x | | 5(2x+13)=25 | | -5(0-6)=0 | | (x-3)/×=96.5 | | x+x+7018.75=280612.06 | | 36-X=52(3) | | 2p^2+9p+10=0 | | 3((3x^2)+(y^2))dx-(2xy)dy=0 | | x+x-7=280612.06 | | (x-3)/×96.5 | | (-3x+2i)(x-6i)=0 | | -3y=9x-7 | | 1.42857x+10=0.375x+3 | | x+10=2000 | | a^3-7a+10bya-2= | | x+x+7=280000 | | 11+4x=-5x+7 |